PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, KOMPENSASI FINANSIAL, DAN KOMUNIKASI INTERNAL TERHADAP KINERJA KARYAWAN PADA UD. KECAK MAMA - Ni Putu Mitha Sri Wahyuni; Anak Agung Dwi Widyani; Ni Made Satya Utami (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2021)
Every company always wants employees to work optimally considering that employees have an important role to play in achieving company success. One of the important elements in an effort to improve employee performance is a leader who is able to actively involve his subordinates in achieving these goals, providing fair and proper financial compensation received by employees in return for services provided to the company and internal communication. The purpose of this study to analyze the effect of transformational leadership, financial compensation and internal communication on employee performance at UD. Kecak mama. The number of samples in this study were 32 employees of UD. Kecak mama, the sampling technique used is the saturated sample method. The analytical tool used to test the hypothesis is multiple linear regression. The results showed that transformational leadership, financial compensation and internal communication have a positive and significant effect on employee performance at UD. Kecak mama. Further research can develop this research by using other variables which theoretically have an influence on employee performance.